The Inequality of Covid–19 Vaccines Distribution: Its Repercussions and Its Causes - Faizi Zaini (International Journal of Business Studies, 2022)
The Covid–19 pandemic has caused not only a harsh health crisis, but also a harsh economic crisis worldwide. Fortunately, new vaccines for Covid-19 have been succesfully developed in the record breaking time. Even though almost every country have started Covid-19 vaccinations for its people, the Covid-19 vaccines distribution remains unequal between high income countries, middle income countries, and low income countries, with high income countries having secured large shipments of Covid-19 vaccines, while middle income countries and low income countries still mostly left behind. This inequality could cause severe repercussions in the form of further Covid-19 virus mutation, the renewal of more countagious and deadlier Covid-19 outbreak, and also a slower recovery of the global economy. The aim of this research is to investigate further about the inequality in Covid–19 vaccines distribution. This research further recommends several policy approach in order to help reduce the inequality of Covid-19 vaccines distribution. This research also aims to contribute to the evolving Covid–19 literature.